Gingival crevicular fluid level of soluble triggering recep-tor expressed on myeloid cells-1(strem-1) in periodontal health and disease: a case-control study - Gigras, Surabhi; Patil, Sudhir R; HR, Veena; Dani, Sneha (International Journal of Dental Research, 2017)
Background: The Triggering Receptor Expressed On Myeloid Cells-1(TREM-1) is a cell-surface receptor of the immunoglobulin superfamily and found to be involved in the amplification of the inflammatory response to various microbial infections, including periodontal diseases.Objectives: The present study was designed to examine gingivalcrevicular fluid(GCF) levels of soluble TREM-1 (sTREM-1) levels in periodontal health and disease as well as evaluate the effect of scaling and/or root planing on the same.Methods: Based on gingival index, probing pocket depth, clinical attachment level, and radiologic parameters (bone loss), 45 subjects were initially divided into three groups- Group, I (Periodontally healthy), Group II (Gingivitis) and Group III (Chronic Periodontitis).From each of the subjects, GCF sample was collected at baseline and scaling and/or root planing was instituted in group II and group III patients. GCF samples were subsequently collected at eight-week interval. Levels of sTREM-1 in collected GCF samples were estimated using enzyme-linked immunosorbent assay.Results: The lowest GCF levels of sTREM-1 were found in periodontal health (69.50±1.8pg/ml) followed by gingivitis (257.17±79pg/ml) and chronic periodontitis (3658.14±55pg/ml) in increasing order, suggesting that levels of sTREM-1 in crevicular fluid increased with the severity of periodontal disease. sTREM-1 levels decreased significantly from baseline to the end of 8 weeks following non-surgical periodontal therapy.Conclusion: Increased GCF levels of sTREM-1 from periodontal health to disease strengthen its association with periodontal status.